Gender Glass Ceiling in Indonesia: Manifestation, Roots, and Theological Breakthrough - Siti Ruhaini Dzuhayatin (Al-Jami'ah Research Centre, 2020)
The Struggle for achieving gender equality has been undertaken in the international and national levels through the commitment of the United Nation (UN) on 30% women quota in politics and public positions. In reality, women are far lag behind due to the so-called ‘gender glass ceiling, a metaphor of ‘invisible barriers refer to ‘glass’ through which women can see higher positions but cannot reach them which is insinuated with ‘ceiling’. The root-causes are deeply rooted in cultural values and social practices whereby patriarchy and religion are dialectically amalgamated. Unless there is a theological breakthrough to a women-friendly interpretations, glass ceiling is unbreakable. This paper aims at examining the extend to which Islamic sholars, especially women in Islamic higher education in Indonesia, contribute to dismatling patriachal biases from religious traditions upholding the glass-ceiling. Before observing the initiatives taken to break the glass ceiling, the paper discusses the phenomenon of manifestation of the existence of the gender glass ceiling and the roots of why the ceiling has been so far upheld. The study reveals that there is a positive correlation between the rising theological discourses voiced by women religious scholars and the vertical mobility of women in public positions as the pathway by then the gender glass ceiling is broken. [Perjuangan kesetaraan gender dilakukan di tingkat internasional maupun nasional dengan komitmen Perserikatan Bangsa-Bangsa tentang kuota 30% bagi perempuan dalam politik dan publik. Pada kenyatannya, perempuan masih tertinggal jauh karena rintangan yang disebut ‘atap kaca’, suatu perumpamaan hambatan yang tidak seperti kaca, perempuan dapat melihat posisi lebih tinggi tetapi sulit menembusnya. Akar masalahnya ada pada nilai budaya dan praktik sosial dan teologi berkelindan. Tanpa ada terobosan teologis yang ramah perempuan, fenomena ‘atap kaca’ sulit dipecahkan. Studi ini menganalisis sejauh manakah kontribusi para intelektual Islam, terutama perempuan di perguruan tinggi Islam di Indonesia mampu menggeser bias dalam tradisi agama yang menguatkan ‘atap kaca’. Sebelum mengkaji upaya-upaya yang dilakukan untuk menggeser atau meruntuhkan atap kaca bias jender, tulisan ini mendiskusikan terlebih dahulu bentuk-bentuk manifestasi keberadaan atau berdirinya atap kaca bias jender dan akar atap tersebut. Dalam studi ini ditemukan korelasi positif antara meningkatnya diskursus teologis yang disuarakan perempuan dan meningkatnya mobilitas vertikal perempuan pada posisi publik yang diharapkan dapat memecahkan atap kaca gender tersebut.]